2016
DOI: 10.1038/ng.3647
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors mediate condensin recruitment and global chromosomal organization in fission yeast

Abstract: It is becoming clear that Structural Maintenance of Chromosomes (SMC) complexes, such as condensin and cohesin, are involved in the three-dimensional genome organization, yet the exact roles of these complexes in the functional organization remain unclear. This study employs the ChIA-PET approach to comprehensively identify genome-wide associations mediated by condensin and cohesin in fission yeast. We find that although cohesin and condensin often bind to the same loci, they direct different association netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(115 citation statements)
references
References 65 publications
5
96
0
Order By: Relevance
“…It has been shown that the fission yeast genome is organized into ~50-kb domains, hereby referred to as small domains 21,27 . The in situ Hi-C approach detected the presence of these small domains consistently during the cell cycle (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the fission yeast genome is organized into ~50-kb domains, hereby referred to as small domains 21,27 . The in situ Hi-C approach detected the presence of these small domains consistently during the cell cycle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has previously been suggested that cohesin is required for the formation of ~50-kb domains 21,27 . We posited that these domains are identical to the stable small domains detected by the in situ Hi-C study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, condensins such as Smc2 are loaded onto SCs to facilitate their segregation (Renshaw et al , 2010; Stephens et al , 2011; Hirano, 2012). In fission yeast, the binding of SMCs modifies the level of chromosome compaction defined as the ratio between long (> 10 kb)‐ and short‐range (< 10 kb) contacts at specific loci (Mizuguchi et al , 2014; Kim et al , 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, computational analyses indicate spatial segregation of replication origins based on their timing of firing during S-phase (4), suggesting that besides local chromatin structure, the 3D organization of chromosomes is an important contributing factor in the spatiotemporal control of replication (5, 6). Despite important advances, understanding the connections between diverse chromosomal events and genome organization remains an important challenge.The complexities of genome organization have been studied in several model organisms, including the fission yeast Schizosaccharomyces pombe, for which the 3D organization has been explored at high resolution (7,8). This simple eukaryote contains the basic chromosomal elements of more complex systems, including partitioning of the genome into euchromatin and heterochromatin domains.…”
mentioning
confidence: 99%
“…The complexities of genome organization have been studied in several model organisms, including the fission yeast Schizosaccharomyces pombe, for which the 3D organization has been explored at high resolution (7,8). This simple eukaryote contains the basic chromosomal elements of more complex systems, including partitioning of the genome into euchromatin and heterochromatin domains.…”
mentioning
confidence: 99%